2022
DOI: 10.1111/bjh.18577
|View full text |Cite
|
Sign up to set email alerts
|

Drug‐induced thrombotic thrombocytopenic purpura: A systematic review and review of European and North American pharmacovigilance data

Abstract: Summary Many medications have been reported to be associated with thrombotic thrombocytopenic purpura (TTP) through pharmacovigilance data and published case reports. Whilst there are existing data available regarding drug‐induced thrombotic microangiopathy, there is no available synthesis of evidence to assess drug‐induced TTP (DI‐TTP). Despite this lack of evidence, patients with TTP are often advised against using many medications due to the theoretical risk of DI‐TTP. This systematic review evaluated the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…11,13 Some observations of drug-induced iTTP involving inhibition of ADAMTS13 and anti-ADAMTS13 antibody have, however, been reported (mainly with anti-platelet ticlopidine withdrawn for the market, rarely with other drugs as prasugrel, clopidogrel, leflunomide, pembrolizumab). 2 The first case of TTP in alemtuzumab-treated patients, requiring ICU and plasmapheresis, was identified in a Finnish nationwide cohort of 121 RR-MS and secondaryprogressive MS patients. 14 No data on clinical manifestations, ADAMTS13 status, time between the administration and the occurrence of the TTP or evolution were available.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11,13 Some observations of drug-induced iTTP involving inhibition of ADAMTS13 and anti-ADAMTS13 antibody have, however, been reported (mainly with anti-platelet ticlopidine withdrawn for the market, rarely with other drugs as prasugrel, clopidogrel, leflunomide, pembrolizumab). 2 The first case of TTP in alemtuzumab-treated patients, requiring ICU and plasmapheresis, was identified in a Finnish nationwide cohort of 121 RR-MS and secondaryprogressive MS patients. 14 No data on clinical manifestations, ADAMTS13 status, time between the administration and the occurrence of the TTP or evolution were available.…”
Section: Discussionmentioning
confidence: 99%
“…Some observations of drug‐induced iTTP involving inhibition of ADAMTS13 and anti‐ADAMTS13 antibody have, however, been reported (mainly with anti‐platelet ticlopidine withdrawn for the market, rarely with other drugs as prasugrel, clopidogrel, leflunomide, pembrolizumab) 2 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3 Using our criteria to evaluate reports of DITMA, 1 which they adapted for evaluating reports of drug-induced TTP (DI-TTP), Scholfield et al recently reviewed 90 reports (describing 97 drugs) that described DI-TTP. 4 They concluded that none of the 97 drugs (including the two drugs and two ICIs that we identified as having probable evidence for causing DI-TTP) had definite or probable evidence for causing TTP. We address this discrepency in this report.…”
mentioning
confidence: 91%